Myo-inositol supplementation improves cardiometabolic factors, anthropometric measures, and liver function in obese patients with non-alcoholic fatty liver disease - Arefhosseini, Sara; Roshanravan, Neda; Tutunchi, Helda; Rostami, Somayyeh; Khoshbaten, Manuchehr; Ebrahimi-Mameghani, Mehrangiz (Frontiers in Nutrition, 2023)
Background Non-alcoholic fatty liver disease (NAFLD) as the hepatic manifestation of metabolic syndrome is closely associated with type 2 diabetes mellitus. Myo-inositol (MI)—a 6-C sugar alcohol—with insulin-mimetic, anti-diabetic, lipid-lowering, and anti-inflammatory properties has exerted favorable effects on insulin resistance-related disorders and metabolic disease, while recent animal studies revealed its positive effects on liver function. This study aimed to investigate the effects of MI supplementation on cardiometabolic factors, anthropometric measures, and liver function in obese patients with NAFLD. Methods This double-blinded placebo-controlled randomized clinical trial was carried out on 48 obese patients with NAFLD who were randomly assigned to either MI (4g/day) or placebo (maltodextrin 4g/day) along with dietary recommendations for 8 weeks. Glycemic indices, lipid profile, liver enzymes anthropometric measures, and blood pressure were evaluated pre- and post-intervention. Dietary intakes were assessed using a 3-day 24 h recall and analyzed by Nutritionist IV software. Insulin resistance was estimated using the homeostasis model assessment of insulin resistance (HOMA-IR), and beta-cell function (HOMA-B) was also estimated. Results Anthropometric measures decreased significantly in both groups, while the reduction in weight (p = 0.049) and systolic blood pressure (p = 0.006) in the MI group was significantly greater than in the placebo group after adjusting for baseline values and energy intake. Although energy and macronutrient intakes decreased significantly in both groups, between-group differences were not significant after adjusting for the potential confounders. MI supplementation led to a significant reduction in serum fasting insulin (p = 0.008) and HOMA-IR (p = 0.046). There were significant improvements in lipid profile, liver enzymes, and aspartate aminotransferase/alanine aminotransferase ratio as well as serum ferritin level in the MI group, compared to the placebo group at the endpoint. By MI supplementation for eight weeks, 1 in 3 patients reduced one- grade in the severity of NAFLD. Conclusion MI supplementation could significantly improve IR, lipid profile, and liver function in patients with NAFLD. Further clinical trials with larger sample sizes, longer duration, different MI doses, and other inositol derivatives are recommended.